The Assessment of Social Distance in Relation to Symptoms of Discrimination in Students' Declarations - Aleksander Sztejnberg; Tadeusz Leszek Jasiński (University of Lower Silesia, 2015)
This article presents the results of a study whose aim was the assessment of social distance in relation to symptoms of discrimination in the first and second years of Physical Education (bachelor's degree) students' declarations. To realize this aim, the authors used the Polish version of Questionnaire "Social Distance - DS," worked out on the basis of the original Bogardus social distance scale. Results showed that students declared the smallest social distance in relation to Catholics (M  = 2,03, SD  = 1,76 - "adherents of religions" category) and the biggest in relation to Roma people (Gypsies) (M  = 5,36, SD  = 1,99 - "persons from definite ethnic and regional group" category). The difference between mean ratings of social distance declared by male and female students in relation to gay men turned out to be statistically significant on level p  < 0,05. The mean rating declared by male students turned out higher from the mean rating declared by female students.